Tumor predisposition: what's the skin got to do with it?. Issue 4 (August 2022) - Stacy, Andrea; Shinawi, Marwan; Coughlin, Carrie C.
Abstract : Purpose of review: Recognition of skin findings associated with tumor predisposition syndromes can prompt early evaluation and surveillance and improve management. Additionally, knowing when to test and when to defer performing genetic testing can streamline management. This article reviews tumor predisposition syndromes with recently characterized skin findings and disorders for which early recognition and counseling can impact the course of disease. Recent findings: Café au lait macules (CALMs) are important in many tumor predisposition syndromes, and 'atypical' CALMs are associated with constitutional mismatch repair deficiency and Fanconi anemia. Melanoma predisposition syndromes caused by pathogenic variants in POT1 and BAP1 are more recently described, and both are associated with Spitzoid tumors. Somatic pathogenic variants can cause segmental nevoid basal cell carcinoma syndrome and a mosaic form of Peutz–Jeghers syndrome. Patients with PTEN hamartoma syndrome have increased risk for melanoma but this might not occur until adulthood. Summary: The cutaneous manifestations of tumor predisposition syndromes can aid diagnosis. Early photoprotection is key to modifying a main risk factor for skin cancer in many of these syndromes. Implementing surveillance guidelines facilitates early detection of tumors.